Yogurt culture : a global look at how to make, bake, sip, and chill the world's creamiest, healthiest food - Rule, Cheryl Sternman (Houghton Mifflin Harcourt, 2015)
Long celebrated as a versatile ingredient in cuisines across the globe, yogurt has recently emerged as a food of nearly unparalleled growth here in the United States. Rule takes yogurt farther than the breakfast table, lunchbox, or gym bag. She strips yogurt of its premixed accessories and brings it back to its pure, wholesome essence. Explore yogurt from every angle, learn how to read a label, and gain entry to the kitchens of cooks from around the world.